PENGELOLAAN LUMBUNG PANGAN MASYARAKAT DESA (LPMD) DI KABUPATEN BOYOLALI - siti dzarroh; kushandajani .; dzunuwanus ghulam manar (Journal of Politic and Government Studies, 2016)
Abstract Food is a basic need and its fulfillment is guaranteed in the Constitution of 1945. The need for food can be met through availability of adequate food with the institutional management of food reserves that communities barns. Management barns of rural communities in the district boyolali aim to find out public food reserve management in Boyolali, identity the role of public related to management of public food reserves and determine management barns in the rural communities that exists in Boyolali may be contained in regulation at the local level. This study used qualitative is descriptive analysis. Sources of data obtained through primary data and secondary data, with data collection using interviews and documents. Management barns in Boyolali far to walk and have a good development, although management methods applied are still likely to be modest, but still be able to sustain the continuity of existing barns. Decision-making by consensus, the high level of trust and transparency characterizes the management of the village community barns in Boyolali. While role of the community in management of barns realized through the support and participation in management services utilizing barns. On the other hand the government through Food Security and the Implementation Guidance Boyolali District preparing a technical policy formulation related to tmanagement of public food reserves in order to support existence of its barns existing in rural communities.Through the management of the village community barns is expected to address food insecurity communities and households Keyword : management , barns villagers , public food reserves